Synthesis and Antiproliferative Activity of Novel Quercetin-1,2,3-Triazole Hybrids using the 1,3-Dipolar Cycloaddition (Click) Reaction - Carreiro, Elisabete P.; Gastalho, Carlos M.; Ernesto, Sofia; Costa, Ana R.; Antunes, Célia M.; Burke, Anthony J. (Synthesis, 2022)
Twenty-three new quercetin-1,2,3-triazole hybrids were synthesized in good to quantitative yields via Cu(I)-catalyzed azide-alkyne cycloaddition reaction under microwave irradiation. These new hybrids contain a 1,4-disubstituted 1,2,3-triazole ring at the 3-OH position of quercetin whilst the remaining hydroxyl groups were either protected as methyl or benzyl groups or left unprotected. All the quercetin-1,2,3-triazole hybrids I–IV were evaluated against REM-134 canine mammary cancer cell line, which is used as a translational model for human breast cancer. These new analogues exhibit potent antiproliferative activity against this cancer cell line. Furthermore, the results show that some of the new quercetin-1,2,3-triazole hybrids have better activity than quercetin. Our best inhibitors displayed IC50 values in the range of 41–180 nM, and undoubtedly will have an important impact on the treatment of both canine and human breast cancer.
Keywords: quercetin; 1,2,3-triazole; Huisgen reaction; molecular hybridization; anticancer; flavonoid